(untitled) (Literasi Nusantara, 2026)
This study examines the role of the state in supporting equal access to higher education by linking constitutional promises and existing realities. This study aims to combine constitutional, fiscal policy, and empirical perspectives on access to higher education to gain a more comprehensive understanding of the existing gaps. Using secondary data analysis methods, it was found that constitutional promises have not been fully realized in terms of equal access to higher education, because the problem of access to higher education in Indonesia cannot be separated from the imbalance between affirmative policies for individuals and the strengthening of institutional funding for higher education. Assistance programs such as KIP-Kuliah have positive potential, but implementation dysfunctions such as inaccurate data validation and disproportionate quota allocation reduce their effectiveness. Limited student assistance and inadequate higher education funding result in the burden of higher education costs being shifted to students. This condition confirms that the realization of constitutional promises in the field of higher education still faces deep structural challenges.